Does an active lifestyle matter? A longitudinal study of physical activity and health-related determinants in older adults - Teraž, Kaja; Pišot, Saša; Šimunic, Boštjan; Pišot, Rado (Frontiers in Public Health, 2022)
Introduction It is well-known that regular physical activity, and thus an active lifestyle, has positive effects on aging and general wellbeing. However, the question remains as to whether regular or increased physical activity can improve self-perception of health status and quality of life in older adults. Methods We conducted a longitudinal study on a group of active older adults between 2013 and 2021. At baseline, i.e., the 1st measurements (baseline), 147 participants were enrolled (mean age 68.4 ± 5.6). After 8 years, in 2021 (follow up), 52 older adults (mean age 75.9 ± 5.3 years) were measured. For the purpose of this study, we included 52 older adults participated at both time-points. For both measurements, participants reported their physical activity and sedentary behavior using the Global physical activity questionnaire (GPAQ), socio-demographic and environmental determinants, recording their self-perception in terms of overall wellbeing. Furthermore, we conducted a qualitative study using semi-structured interviews to obtain subjective data on the changes and events that may have affected physical abilities and general health over an 8-year period. Results At the follow up, participants reported lower physical activity and sedentary behavior compared to baseline, but still met health-enhancing physical activity (HEPA) standards for total self-reported physical activity (>3,000 METmin/week). In addition, they rated their overall health (p < 0.001), physical fitness (p < 0.001), psychological wellbeing (p < 0.001) and overall quality of life (p < 0.001) as better. The qualitative data confirmed that the 8-year period involved changes in physical activity. Specifically, they have continued to carry out physical work (gardening, working in the vineyards, olive groves), but previously organized physical activities were replaced by walks in nature, which probably also influenced the reduction of sedentary behavior. Conclusion After 8 years, as expected, participants reported a decrease in physical activity and a lower level of sedentary behavior. It appears from the interview that healthy older adults filled their days with daily tasks and found more time for walking. Individuals who were more active in the past 8 years also reported better overall health and wellbeing. Selected variables correlated with an active lifestyle and better perceptions of quality of life.